Analysis of the role of General Practice in preventing Avoidable Hospitalisation through a multilevel approach (Epidemiology, Biostatistics, and Public Health, 2022)
Objective. To examine the relationship between Avoidable Hospitalisation (AH) and the activities of General Practitioners (GPs). The study was carried out in the Lazio Region (Italy) within different organizational models of primary care (PC) delivery.Methods: Secondary data of a set of GP activities delivered to the Lazio population as listed in the Lazio GPs in 2008, were used. For each GP a set of health services delivered to the patients on their practice lists were measured. The relation between the rates of AH, acute and chronic conditions separately, and the rates of such health services were analyzed through the use of a multilevel Poisson regression model, adjusted according to patients’ health status.Results: The study included data from all the active GPs (4,837) in the Lazio Region and their 4,666,037 registered patients. The overall AH rate of the registered patients was 7.7 per 1,000, 2.2 for acute and 5.5 for chronic conditions. The diagnostics prescription by GPs is associated with a 7% (IRR=0.93;95% C.I.:0.89-0.97) reduction of the chronic AH rate. Patients registered at GPs working within a team practice resulted in a hospitalisation rate decrease of 5% (IRR= 0.95; 95% C.I.:0.91-0.99)  for avoidable acute conditions.Conclusion: The study showed that the role of GPs in preventing AH is substantial, particularly when team practice is performed and specifically when additional diagnostics are prescribed. The study is further evidence in favor of the validity of AH as an outcome measure of quality and accessibility of primary care.